High throughput screening for inhibitors of the HECT ubiquitin E3 ligase ITCH identifies antidepressant drugs as regulators of autophagy - Rossi, Mario (2014)
Inhibition of distinct ubiquitin E3 ligases might represent a powerful therapeutic tool. ITCH is a HECT domain-containing E3 ligase that promotes the ubiquitylation and degradation of several proteins, including p73, p63, c-Jun, JunB, Notch and c-FLIP, thus affecting cell fate. Accordingly, ITCH depletion potentiates the effect of chemotherapeutic drugs, revealing ITCH as a potential pharmacological target in cancer therapy. Using high throughput screening of ITCH auto-ubiquitylation, we identified several putative ITCH inhibitors, one of which is clomipramine--a clinically useful antidepressant drug. Previously, we have shown that clomipramine inhibits autophagy by blocking autophagolysosomal fluxes and thus could potentiate chemotherapy in vitro. Here, we found that clomipramine specifically blocks ITCH auto-ubiquitylation, as well as p73 ubiquitylation. By screening structural homologs of clomipramine, we identified several ITCH inhibitors and putative molecular moieties that are essential for ITCH inhibition. Treating a panel of breast, prostate and bladder cancer cell lines with clomipramine, or its homologs, we found that they reduce cancer cell growth, and synergize with gemcitabine or mitomycin in killing cancer cells by blocking autophagy. We also discuss a potential mechanism of inhibition. Together, our study (i) demonstrates the feasibility of using high throughput screening to identify E3 ligase inhibitors and (ii) provides insight into how clomipramine and its structural homologs might interfere with ITCH and other HECT E3 ligase catalytic activity in (iii) potentiating chemotherapy by regulating autophagic fluxes. These results may have direct clinical applications.